Urgensi Calon Independen Dalam PemlUhan Kepala Daerah Langsung - elsa fais (Jurnal Hukum IUS QUIA IUSTUM, 2006)
If the Election Head of Region can be used as a momentum of fundamental change, thus the attendence of independent candidate is absolute and cannot be bargained. Practically and theorethically, independent candidate is significant.